2018
DOI: 10.3390/su10030647
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Effects of Urban Expansion on Terrestrial Carbon Storage: A Case Study in Xuzhou City, China

Abstract: Carbon storage is closely connected to the productivities and climate regulation capacities of ecosystems. Assessing the effects of urban expansion on carbon storage has become increasingly important for achieving urban sustainability. This study analyzed the effects of urban expansion on terrestrial carbon storage in Xuzhou City, China during 2000-2025. The cellular automata (CA) model was developed to simulate future urban expansion under three scenarios, namely, the business as usual (BAU), ecological prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 35 publications
1
15
0
Order By: Relevance
“…In this study, we found that the maximum carbon stock losses occurred in the developing urban areas ( Figures 5-7). This result is consistent with the results of [41,55]. In locations characterized by rapid urbanization, the increase in the built-up area occurs at the cost of occupying other land use types, such as cultivated land, water, and forest [59,60].…”
Section: Spatiotemporal Changes In Carbon Storage Due To Urbanizationsupporting
confidence: 89%
See 2 more Smart Citations
“…In this study, we found that the maximum carbon stock losses occurred in the developing urban areas ( Figures 5-7). This result is consistent with the results of [41,55]. In locations characterized by rapid urbanization, the increase in the built-up area occurs at the cost of occupying other land use types, such as cultivated land, water, and forest [59,60].…”
Section: Spatiotemporal Changes In Carbon Storage Due To Urbanizationsupporting
confidence: 89%
“…Urbanization brings population and economic growth, but it also leads to ecological problems [43][44][45]. Many studies have shown that urbanization has an impact on carbon storage in terrestrial ecosystems [36][37][38][39][40][41]. In contrast to previous studies, this study comprehensively analyzes the "spatial" and "temporal" changes in carbon stocks from the urbanization process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the US, Lavy et al (2016) studied impacts of urban sprawl, showing mixed impacts on soil carbon. In China, Li et al (2018) and He et al (2016) both showed large scale carbon loss due to urban expansion of Xuzhou City and Beijing respectively. However, in Moscow a modelling study estimated potential increases in urban soil carbon resulting from high carbon storage in areas of urban greenspace (Vasenev et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The world is experiencing significant urban expansion, which is likely to continue in the future [1,2], that had caused global land landscape alteration resulting from land use/land cover (LULC) change. Rapidly urbanizing regions with deforestation largely reduce the provision of ecosystem service, especially service related to carbon that LULC change is one of the most important source of CO 2 emissions [1,3,4]. Regional carbon storage was greatly affected due to the increase of built-up land and the loss of natural vegetation, which seriously threatens the provision of regional ecosystem services and sustainability.…”
Section: Introductionmentioning
confidence: 99%